Dynamic GNNs for Predicting Train Cancellations on the Dutch Railway Network: A Multi-Season Study of Environmental and Operational Factors - Brakenhoff, Brent; Alsahag, Ali Mohammed Mansoor; Ziabari, Seyed Sahand Mohammadi (Digital Technologies Research and Applications, 2026)
Cancellations on the Dutch Railway network are a common and unpredictable occurrence; however, little research has focused on predicting these cancellations. Previous studies on the Dutch railway system have primarily concentrated on delay prediction. For this regression task, models such as XGBoost, Random Forest, Long Short-Term Memory (LSTM), and Gradient Boosting Decision Tree have been shown to perform well. Graph neural network-based models have been used for regression tasks on other transportation networks. We propose a Dynamic Graph Neural Network (DGNN) combined with an LSTM network for binary classification of cancelled trajectories. We compare the model with baseline models on a seasonal split to compare the feature importance across different seasons. Model performance is gauged using paired t-tests on bootstrapped F1 scores. Additionally, Precision, Recall, Balanced Accuracy, and AUC are considered metrics for further comparison. The newly proposed features achieve mostly positive feature importance scores across the models. Amongst the evaluated models, the proposed DGNN and XGBoost outperform the baseline models. Overall, the models underperform with F1 scores no higher than 0.4. This paper provides insight into the influence of various weather and operational features on cancellations on the Dutch railway network, with the operational features proving insightful.